Effect of two different manual therapy techniques for treatment of forward head posture: A comparative study - Hassan, Shaza S.; Hatem Ameen, Fairouz; Draz, Amira H.; Abdel Raouf, Neveen A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Background: Forward head posture (FHP) is a misalignment of the head on trunk that makes the external moment longer by shifting the gravitational center in front of the load bearing axis causing stress on the suboccipital muscles with functional movement limitations and formation of myofascial trigger points (MTrPs). Objectives: To compare between suboccipital muscle inhibition technique (SMIT) and progressive pressure release technique (PPRT) on craniovertebral angle (CVA) and neck range of motion (ROM) in individuals with FHP and active suboccipital MTrPs. Methods: Forty-five subjects were randomly assigned in three groups. Group A was given postural correction exercise, group B received SMIT and postural correction exercise, and group C received suboccipital PPRT and postural correction exercise. Results: Statistical significance was found within and between groups in respect to ROM in all directions (P < 0.05) except for right and left side bending between groups A and B, which was P = 0.54 and P = 0.67, respectively. CVA had shown significant results for within and between groups (P < 0.05) except for group A versus group B (P = 0.41). Conclusion: Both techniques work to increase CVA and improve ROM in individuals with FHP. However, suboccipital PPRT has shown to be more effective.